STOCK ASSESSMENT AND BIOLOGY OF JOHNIUS GLAUCUS (DAY) OFF THE NORTHWEST COAST OF INDIA - DEVARAJ, M.; KAMAT, S. S. (Journal of Indian Fisheries Association, 2015)
The stock size and biology of Johnius glaucus (Day) resource off thenorthwest coast of India were studied for 1982-83 and 1983-84. The totallength at the end of 6, 12, 18, 24 and 26 months was 121 mm, 183 mm, 237mm, 261 mm and 264 mm respectively. The length growth parameterswere : Loo = 300 mm, K ::::: 0.0807 (monthly) and t 0 = -0.51 month. The weightgrowth parameters were : Woo = 317g, K = 0.0762 (monthly) and t 0 = -0.41month. The exploited stock mainly composed of 1/2 +and 1+ age groups.The annual Z, M and F were 2.34, 1.49 and 0.85 respectively. The lb, tb, lr,tr and selection factor K were 155 mm, 0.75 year, 65 mm, 0.25 year and3.875 respectively. The Yw/R was optimum at the exploitation rate (E) of0. 75 and codend mesh size of 37 mm. The total stock for 1982-83 and1983-84 was 14,624 and 26,190 tons respectively. The standing stock of1982-83 -and 1983-84 was 5,645 and 10,110 tons respectively. The MSY for1982-83 and 1983-84 was 6,623 and 11,788 tons respectively. The F and Zwas lowest in 0+ age group and highest in 1+ age group.